Effect of dental antiseptic agents on the viability of human periodontal ligament cells - Zambaga Khorolsuren; Orsolya Lang; Janos Vag; Laszlo Kohidai (Elsevier, 2021)
Objectives: We aimed to study whether or not various dental antiseptic agents affect the viability and proliferation of human periodontal ligament cells (PDLCs). Materials and methods: Human PDLCs were isolated from a total of 10 surgically extracted impacted third molars and were.cultured in-vitro. The cells were exposed to commonly used dental antiseptics, including chlorhexidine, cetylpyridinium chloride, triclosan, povidone-iodine and sodium bicarbonate for ultra-short-term (10, 20, 30 sec), short-term (10, 20, 30 min) and long-term (24, 48 h) at various concentrations. Cell morphology was observed with light microscopy. Cell viability was studied with impedimetric real-time xCELLigence and resazurin-based alamarBlue® assays. We used one-way ANOVA with Tukey's and Bonferroni test (p < 0.05) for statistical analysis. Results: Both alamarBlue® and xCELLigence analysis results were in agreement that ultra-short-term contact with cetylpyridinium chloride ≥ 0.01 mg/ml, chlorhexidine ≥ 1 mg/ml, triclosan ≥ 1 mg/ml and povidone-iodine ≥ 1 mg/ml as well as long-term exposure to cetylpyridinium chloride ≥ 0.001 mg/ml, chlorhexidine ≥ 0.01 mg/ml, triclosan ≥ 1 mg/ml, povidone-iodine ≥ 1 mg/ml and sodium bicarbonate ≥ 10 mg/ml was able to reduce the viability of human PDLCs significantly. According to the half-maximal inhibitory concentration (IC50) the rank of cytotoxicity was cetylpyridinium chloride > chlorhexidine > triclosan > povidone-iodine > sodium bicarbonate. Conclusions: Our findings suggest that the tested antiseptic agents were cytotoxic to human PDLCs at lower than practically applied concentrations in dental interventions.